Legal and ethical dilemma in treating trauma patients - D., Srinivasan; P. N., Sreeramulu; Dave, Prakash; Sathanantham, Dinesh Kumar (International Surgery Journal, 2018)
Background: The severity of the injury may be such that ongoing care of the individual patient is futile, and this can lead to disagreement with the family or friends of the patient with regard to further treatment. Patient capacity or ability to participate in the informed consent process may be compromised and the patient is therefore managed by the clinical team on the basis of the best interest’s principle, with clinicians relying on proxy consent or substituted judgment. These sections of the hospital have their own ethical and medico-legal issues for the trauma patient and the treating clinician. The aims and objectives were to estimate the time of triage/ specialist care given in the Emergency Medical department (EMD) in Trauma case; to compare the result with Australasian triage scale and Manchester triage scale system and to study about the demography and audit the necessary findings from trauma patients in casualty. Methods: This is a Prospective observational study done at R. L. Jalappa Hospital a constituent of Sri Devaraj Urs Medical College and Research, Kolar, Karnataka a rural based tertiary teaching hospital. Results: A total of n=108 patients were evaluated in this study, severity of the injury was moderate been the highest with 52 (48%), severe been 33 (30.6%), mild been 20 (18.5%). Majority of the injury was in the age group 21-40, mostly been the major working population and bread winners involved in the Road traffic accidents. Mean time of specialist (surgeon) attending to the case was 70 minutes i.e. the interval between CMO and consultant attending to the trauma case in EMD. Conclusions: Management of Trauma patients involves very meticulous work which can be achieved only with proper team-work and planning protocol and the more important aspects towards the management involves the documentation and proper communication with patient attendants and responsible persons. On concluding, the triage system followed in our setup with specialist care been provided is equal in its efficacy in comparison to the Manchester triage scale and is almost in par with the Australasian triage scale.